The stages of economic growth; a non-communist manifesto - Rostow, W. W. (Cambridge [Eng.] University Press, 1971)
The book is an effort to map a large problem. It is not an encyclopedia of economic history.
Includes bibliographical references.
osc 3/11/2021
Loans
Keywords: Economic development; Capitalism; Marxian economics; Comparative economics